PATHOGENETIC MECHANISMS OF THE DEVELOPMENT OF ISCHEMIC AND REPERFUSION DAMAGE THE KIDNEYS AS A PROMISING TARGET SPECIFIC THERAPY - A. V. Vatazin; I. V. Nesterenko; A. B. Zulkarnaev; N. L. Shakhov (Вестник трансплантологии и искусственных органов)
Ischemic and reperfusion injury is a complex, multifactorial process that damage kidney transplant. Knowledge and understanding of pathogenic mechanisms of damage processes allows the use of various biological agents to reduce this damage. However, the application of most of biological agents is still only in the experiment. The purpose of this survey show participants of pathogenetic mechanisms, mainly inflammatory mediators (cytokines, chemokines), their interactions, and the consequences of their damaging effects on the fabric kidney transplant.